SPATIAL CONCENTRATION OF THE MANUFACTURING INDUSTRY: EVIDENCE FROM RUSSIA - Maslikhina, Veronika (Journal of Applied Engineering Science, 2017)
Spatial concentration of the manufacturing industry in Russia during the period of 2005-2015 was analyzed in the article. The analysis includes 83 Russian subjects, which are united in 8 federal districts. The Herfindahl-Hirschman index, the Theil index and the coefficient of variation by the production volume, the number of employees and the fixed assets volume were used to estimate the scale and tendencies of the spatial concentration of the manufacturing industry. The analysis has revealed an increase in the spatial concentration of the manufacturing industry in Russia as a whole against the backdrop of multidirectional concentration-dispersion processes in the regions and districts. Production redistribution has been revealed: the east of the country is dominated by the deconcentration of production and the western part is dominated by the concentration of production. The strong localization of certain sectors of the manufacturing industry (chemical and electronic industry, and transport vehicles production) under the influence of agglomeration forces has been established.
Keywords: the coefficient of variation; the Theil index; the Herfindahl-Hirschman index; Russia; agglomeration process; manufacturing industry; spatial concentration